Akanthomyces araneicola, a new araneogenous species from Southwest China - Chen, Wan-Hao; Liu, Chang; Han, Yan-Feng; Liang, Jian-Dong; Tian, Wei-Yi; Liang, Zong-Qi (Phytotaxa, 2019)
During a survey of spider-pathogenic fungi from Southwest China, a new araneogenous species was found. The new species, Akanthomyces araneicola, differs from other species based on mostly smaller fusiform conidia (2.5–5.0 × 1.3–1.9 μm), mononematous conidiophores and, additionally, in parasitising a spider. Both the morphological identification and phylogenetic analysis of combined ITS, LSU, RPB1, RPB2 and TEF sequence data support A. araneicola as a new species in the genus Akanthomyces.